Expansion of MIR482/2118 by a class‐II transposable element in cotton. (11th July 2020) - Shen, Enhui; Chen, Tianzi; Zhu, Xintian; Fan, Longjiang; Sun, Jie; Llewellyn, Danny J.; Wilson, Iain; Zhu, Qian‐Hao
SUMMARY: Some plant microRNA (miRNA) families contain multiple members generating identical or highly similar mature miRNA variants. Mechanisms underlying the expansion of miRNA families remain elusive, although tandem and/or segmental duplications have been proposed. In this study of two tetraploid cottons, Gossypium hirsutum and Gossypium barbadense, and their extant diploid progenitors, Gossypium arboreum and Gossypium raimondii, we investigated the gain and loss of members of the miR482/2118 superfamily, which modulates the expression of nucleotide‐binding site leucine‐rich repeat ( NBS‐LRR ) disease resistance genes. We found significant expansion of MIR482/2118d in G. barbadense, G. hirsutum and G. raimondii, but not in G. arboreum . Several newly expanded MIR482/2118d loci have mutated to produce different miR482/2118 variants with altered target‐gene specificity. Based on detailed analysis of sequences flanking these MIR482/2118 loci, we found that this expansion of MIR482/2118d and its derivatives resulted from an initial capture of an MIR482/2118d by a class‐II DNA transposable element (TE) in G. raimondii prior to the tetraploidization event, followed by transposition to new genomic locations in G. barbadense, G. hirsutum and G. raimondii . The 'GosTE' involved in the capture and proliferation of MIR482/2118d and its derivatives belongs to the PIF/Harbinger superfamily, generating a 3‐bp target site duplication upon insertion at new locations. All orthologous MIR482/2118 loci in the two diploids were retained in the two tetraploids, but mutation(s) in miR482/2118 were observed across all four species as well as in different cultivars of both G. barbadense and G. hirsutum, suggesting a dynamic co‐evolution of miR482/2118 and its NBS‐LRR targets. Our results provide fresh insights into the mechanisms contributing to MIRNA proliferation and enrich our knowledge on TEs. Significance Statement: This study discovered expansion of the MIR482/2118 family in cotton through the capture of MIR482/2118d by a DNA transposable element following proliferation of the transposable element with the captured MIR482/2118d, and demonstrated the dynamic co‐evolution of miR482/2118 and its target NBS‐LRR genes by finding species‐ and cultivar‐specific miR482/2118 isoforms.